الأمن الثقافي: محاذير العولمة الثقافية وسبل المقاومة - عابد, يسمينة; جحيش, يوسف (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
نتج عن التأثير التراكمي للعولمة ثورة على السيادة في جميع المجالات؛ ففي المجال السياسي هناك محاولة للقضاء على سيادة الدول وظهور بوادر الحكم العالمي، وكذا عولمة الاقتصاد الذي يرتكز على الشركات المتعددة الجنسيات في إطار النظام الرأسمالي، والتي تهدف إلى تعميم القيم الاقتصادية، وامتداد تلك التأثيرات إلى ثقافات الدول للقضاء على مبدأ السيادة الثقافية، مما أدى إلى تغيرات في النظام القيمي ، وبذلك أصبح الأمن الثقافي هو أكبر تحدي يواجه المجتمعات في حماية ثروتها المعنوية في ظل عنفوان العولمة الثقافية. The cumulative influence of globalisation had resulted a revolution on sovereignty in all aspects, in the political aspect there is an attempt to eliminate nation's sovereignty and the appearance of the new world order signs , also the economic globalisation that centers on multi national companies within capitalist system, that aims to generalising the economic values, expansion those effects to countries cultures to eliminate the cultural sovereignty principle, which led to changes in value system, so that the cultural security became the biggest challenge that. faces societies in protection their spiritual fortune within cultural globalisation influence.